SOCIAL ENTREPRENEURSHIP: CRACKING THE UNKNOWN PHENOMENON OF INDIVIDUALS WITH AUTISM SPECTRUM DISORDER (Jurnal Pembangunan Sosial, 2024)
Despite numerous initiatives made by various organisations to increase employment opportunities for individuals with autism spectrum disorder (ASD), they remain unemployed. The unemployment rate for individuals with ASD remains high. Therefore, this study seeks to understand the employment challenges for individuals with ASD and develop innovative solutions to address them. This study selected six founders of social enterprises in Klang Valley, Malaysia, that target individuals with ASD as participants. The study uses a face-to-face interview as a means of data collection. By implementing the thematic analysis, the study will uncover key themes and patterns that can inform future initiatives and policies to promote inclusion and diversity in the Malaysian workforce. These findings will contribute to a more comprehensive understanding of the challenges faced by marginalised groups and the strategies that can be implemented to address them effectively.